Surface protein glycosylation conserved in the human pathogen Mycoplasma genitalium and retained in the synthetic organism JCVI-Syn3A - John William Sanford; James Mobley; Kevin Dybvig; Thomas Prescott Atkinson; James Michael Daubenspeck (PLoS ONE, 2025)
Protein glycosylation has been reported in all forms of life. The genus Mycoplasma is composed of highly genome-streamlined bacterial symbionts, making them model organisms for investigating minimal genome concepts. Previous work from our group showed mycoplasmas scavenge hexoses from exogenous oligosaccharides to glycosylate surface proteins at serine, threonine, asparagine, and glutamine residues without utilizing a consensus sequence as seen in canonical glycosylation systems. We report here that this surface protein hexosylation system is conserved in Mycoplasma genitalium, a human urogenital pathogen with a 580-kbp genome that can be cultured axenically. We also report this modification is found in the ruminant pathogen Mycoplasma mycoides subsp. capri and is conserved in JCVI-Syn3A, a nonpathogenic mycoplasma with a synthetic minimal M. mycoides genome containing genes that are essential for survival and robust growth under axenic culture conditions. In contrast to known glycoproteins, we have detected evidence of glycosylation of aspartic acid and glutamic acid residues, which expands the pool of potential glycosyl acceptors in bacteria to include the acidic amino acids.